2004
DOI: 10.1111/j.1471-1842.2004.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methodological search filters—a review

Abstract: Awareness of the process and limitations involved in search filter development is essential to make an informed decision on the applicability and validity of search filters. The findings of this review indicate a considerable agenda for future research, in particular, to improve the quality of reporting of search filters and to inform users on their use and application. Based on the review, guidance in the appraisal process of search filters is given in the form of a checklist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
296
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(310 citation statements)
references
References 36 publications
1
296
0
2
Order By: Relevance
“…Work is required to test and validate our search filter against an established gold standard. This requires the identification of publications by hand searching a range of target journals 18 to determine and optimize the sensitivity, specificity, precision, and accuracy. Subsequently, it will be possible to refine the search terms to produce a 'second generation' subject search filter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Work is required to test and validate our search filter against an established gold standard. This requires the identification of publications by hand searching a range of target journals 18 to determine and optimize the sensitivity, specificity, precision, and accuracy. Subsequently, it will be possible to refine the search terms to produce a 'second generation' subject search filter.…”
Section: Discussionmentioning
confidence: 99%
“…Search filters were initially developed in the 1990s to help researchers identify publications pertaining to particular methodological designs, such as prevention, diagnosis, treatment, prognosis, systematic reviews, and randomized controlled trials. [16][17][18] It was beyond the scope and intent of this project to review all the articles identified using our search filter. What we set out to achieve by making the comparison with the general search results was to highlight the potential to miss many relevant publications if a suboptimal search strategy is used.…”
Section: Subject Search Filter For Spinal Cord Damage Not Due To Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…They manage the search process in its entirety, from designing the search strategy to conducting and documenting the actual search and managing the references [2]. Information specialists also develop search filters that enable the efficient searching of bibliographic databases for specific methodological and subject-specific research questions [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Filters are objectively derived, pretested strategies optimized to help users efficiently retrieve articles for a specific purpose. 7,8 PubMed provides two types of clinical search filters: methods-based and topic-based. Methodsbased filters (known as clinical queries) were designed to retrieve articles on therapy, diagnosis, prognosis and etiology.…”
mentioning
confidence: 99%